Materiality in Roman Art and Architecture - Haug, Annette; Hielscher, Adrian; Lauritsen, Michael Taylor (Decorative Principles in Late Republican and Early Imperial Italy (Decor), 2021)
Material is the substance of the world of things. Literary sources suggest that materiality was part of aesthetic perception, loaded with meaning and bound to function even in antiquity. To date, this complex reading of material has not been adequately represented in archaeological research. The present volume addresses this oversight by examining the decorative use of material in Roman Italy between the Late Republic and Early Imperial period.